‘Integration of Peace Education: The Role of Values, School Curriculum and Teachers in Inculcating Peace Education’ - Tariq Mehmood Bhuttah, Samina Sarwat, Faiz Farid,ZhanYongQi, Amna Bibi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Contemporary world is facing a colossal problem of unrest and chaos that influenced the economic, political and social system of the country. In this context the endorsement of peace in educational sectors has become increasingly important. There are demands and a need to include peace education in curricula at school level so that the problem of unrest could be mitigated in society. The overall debate of this study is upon the question that how we can make peace and how we can reach to peace? It is discuss throughout the research that Peace is an essential value that every person must respect. Thus the major goal and chief purpose of education is inculcating peace. Therefore, peace education must be aimed at addressing the root causes of conflicts i.e. divisions basing on race, class, caste, and sect. To upgrade the situation, a long-term and positive peace is required. In this context, teacher, school and curriculum can played a marvelous role in promoting peace in society. This study is significant because it helps the teachers to understand the concept of peace education and its importance for students and teachers, help the students to raise their moral behavior, provides strategies that will help the teachers and students to make the environment of school peaceful, help the government to analyze the curricula and make improvements in peace education in students and teachers.